LEGAL REGULATION OF INCEST IN INDIA - BUKALEROV S.A.; CHUKREEV V.A. (Legal Bulletin)
A survey in India found out that one in two children had been sexually abused at least once before the age of 18, and 90% in the family or inner circle. There were 24,672 incidents of sexual abuse of minors in 2019. The Protection of Children from Sexual Offenses Act of India 2012, also known as POCSO, was enacted in India to protect children from sexual assault, sexual harassment and stop the use of children in pornography. The article analyzes the provisions of this law and the practice that has developed in Indian society. The purpose of the article is to analyze the provisions of this law and the practice that has actually developed in Indian society in order to study the features of rule-making and law enforcement in India. There are no laws in India’s legal system that specifically mention incest as an offence. Data provided by the National Crime Records Bureau in India shows that sexual crimes against women and children are increasing every year. Given this, it is concluded that despite the attempts of the Indian legislator to fill the existing loopholes, the measures taken are insufficient and India is far from solving the problem of incest.